Beneath the surface: gut microbes, cyathostomins and resident immune cells – Characterising the baseline - Yerlikaya, Zeynep; Miranda-CasoLuengo, Raúl; Jahns, Hanne; Byrne, Orla; Meijer, Wim G.; Mulcahy, Grace; Walshe, Nikki (Elsevier Ltd, 2025)
Cyathostomins are the most prevalent and currently considered the most pathogenic gastrointestinal nematodes in horses. Their life cycle includes an encystment phase within the large intestinal mucosa, where up to 90 % of the total worm burden resides. Clinical disease ranges from chronic protein-losing enteropathy to acute, sometimes fatal, typhlocolitis. Despite their significance, the ecological interplay between cyathostomins, the host immune response, and the gut microbiota remains poorly understood. To our knowledge, this is the first study to investigate these interactions at the mucosal level. Eleven horses were randomly selected from an abattoir survey. Samples were collected from the caecum, right ventral colon, and left dorsal colon. Parasitological assessments included faecal egg counts, luminal worm enumeration, and mucosal larval counts. Immunological analysis comprised histopathology and immunohistochemistry, while microbiota profiling was performed using bioinformatics. All horses were infected with cyathostomins, including those with zero faecal egg counts. Mucosal larval burdens were highest in the caecum and right ventral colon, while luminal adult worms predominated in the ventral and dorsal colon. T lymphocytes and macrophages were the dominant immune cells in the mucosa; eosinophils and goblet cell hyperplasia showed no correlation with parasite load. Larval invasion of the submucosa was observed only in horses with high mucosal burdens, suggesting density-dependent tissue penetration. Microbiota analysis revealed increasing divergence along the intestinal tract, with caecal and faecal samples showing the greatest differences. These findings highlight regional specialization and suggest that faecal samples may not accurately reflect mucosal microbiota composition. This descriptive study provides novel insights into the spatial dynamics of cyathostomin infection, mucosal immunity, and microbiota composition in the equine large intestine, offering a foundation for future research into equine gastrointestinal health and parasitology. Copyright © 2025. Published by Elsevier Ltd.
Keywords: Cyathostomins; Equine gastrointestinal ecosystem; Gut microbiota; Larval encystment; Mucosal immunity; Parasitic burden